Comparative Evaluation of Apical Fit of Various Corresponding Gutta-percha Cones in Prepared S-shaped Canals of Simulated Mandibular Premolars: An In-vitro Study - Parul Bansal; Garima Singh; Mohit Kumar; Nikita Sharma; Smrity Sinha; Darshana Baruah (Journal of Clinical and Diagnostic Research)
Introduction: The goal of root canal obturation is to completely seal the root canal system in three dimensions, in order to stop the recurrence of bacterial infections. Root canal curvatures may be apical, gradual, sickle-shaped, severe-moderate-straight curve, bayonet/S-shaped curve and dilacerated curve. Curved root canals exhibit great difficulty in cleaning, shaping and obturation of the root canal system. Normally, corresponding Gutta-percha (GP) as per the file systems are used but what is seen is that GP’s don’t fit properly sometimes. So, this study was done to evaluate the apical fit of four corresponding size GP points by keeping the same/ standard endodontic file system in prepared simulated canals. Aim: To evaluate the apical fit of various corresponding GP cones in prepared S-shaped canals of simulated mandibular premolars. Materials and Methods: The present In-vitro study was conducted at Shree Bankey Bihari Dental College, Ghaziabad, Uttar Pradesh, India for a period of one month starting from August to September 2023. After the approval of the Ethical Research Committee at Shree Bihari Dental College. A total of 40 simulated mandibular premolar models, having S-shaped canal morphology were taken. E3 Azure Files (Endostar, Poland) were used to prepare root canals. The rotational speed was set to 300 rpm and 2.5 Nm of torque. Each model’s orifice was widened with an orifice opener (30/08), and then a Glide file until the Working Length (WL) was determined. The sequence used for canal enlargement was 20/04, followed by 20/06 rotary file, in a Clockwise (CW) and Counterclockwise (CCW) motion. Every tooth was prepared from the crown down, with an apical size of 20 mm with 0.06 taper. To remove debris, saline irrigation was applied to the models in combination with an ultrasonic activator. Each time a file was changed, irrigation was performed. Paper points were used to dry the canals (Dentsply). The models were then divided into four groups based on the different GP points; Group 1 (n=10) Diadent, Group 2 (n=10) Hygenic, Group 3 (n=10) Dentsply, Group 4 (n=10) META. The apical fit of GP cones in all the models was assessed using Cone Beam Computed Tomography (CBCT). The obtained results were tabulated (One-way ANOVA and Post-hoc Tukey tests, p-value ≤0.0001, (highly significant) and subjected to statistical analysis using Statistical Package for Social Sciences (SPSS) Software. Results: The apical fit of GP cones in all the models was assessed by distance vbetween the end of GP and the prepared canal (in mm) using CBCT. Highest mean value was present among group 3 Dentsply 0.58±18 and least mean value was among group-2 hygenic (0.03±0.04). Among the groups used, Group 2 hygenic GP points showed less discrepancy in apical fit followed by META, Diadent and then Dentsply where the p-value was ≤0.0001, indicating the result to be highly significant. Conclusion: Based on the findings of this study, it can be concluded that Hygenic GP provided the best fit among the materials tested, followed by META, Diadent, and Dentsply. Further research with broader parameters may be necessary to validate these findings across different conditions.